Taking a Stand : Essays in honour of John Beckwith - McGee, Timothy J. (Timothy James), 1936-; Beckwith, John (Book collections on Project MUSE., 2018)
The essays reflect the variety of musical culture in our country. The music of Canada - past and present; popular, folk, and classical; its creators, collectors, and educators - is presented, discussed, and analysed by prominent scholars. Collectively the essays summarize the current state of research on Canadian music; individually they provide standards, patterns, approaches, and directions for future research.